Bone penetrance of locally administered vancomycin powder in a rat femur fracture model. Issue 7 (July 2017) - Working, Zachary M.; Frederiksen, Hunter; Drew, Alex; Loc-Carrillo, Catherine; Kubiak, Erik N.
Abstract: Introduction: Locally delivered, crystalline vancomycin has been suggested as a potential prophylactic measure against the development of deep and superficial surgical site infection. Clinical expectations regarding the duration and peak of drug concentration in local tissues following administration are unknown. Our goal was to develop concentration vs time curves for locally administered vancomycin powder in a high-energy, open femur fracture rat model in local tissues and to compare that data to two well performed similar, systemic administration studies. Methods: After approval for animal research, 24 adult Sprague-Dawley rats sustained closed, midshaft femoral fracture under anesthesia. Fractures were caused via blunt guillotine with 750 g metal rod dropped 50 cm. Injured hindlimbs were surgically opened at fracture to simulate open injury and stabilized using 0.054 Kirschner wires. Vancomycin powder was administered using weight-based protocol (goal: 25 mg/kg). Rats were sacrificed in groups of 4 at 4, 8, 24, 48, 72, 96 h. Samples harvested included rat-tail venous blood prior to sacrifice, and femoral bone and anterior thigh soft-tissue were harvested post-mortem. High Performance Liquid Chromatography (HPLC) was performed on all samples. Results: Concentration vs. time curves demonstrated that the surrounding soft-tissues demonstrated highest maximum concentration (1.5 mg vancomycin/g muscle). Bone reached maximum average of 199 μg vancomycin/g femur: approximately 13% of maximal soft-tissue absorption. Plasma reached maximum concentration of 1.8 μg/mL plasma. All peaks at t = 4 h. Within 48 h, average muscle vancomycin concentration dropped to 3 μg/g muscle (0.2% maximum muscle concentration) and the average bone concentration dropped to 1.9 μg/g femur (0.9% maximum bone concentration). Vancomycin was undetectable on all samples at 96 h. Comparison to classical animal studies suggest local delivery to bone exceeds that of IV dosing for approximately 48 h and may peak near concentrations of 10 2 multiples. Conclusions: Locally administered vancomycin provides drug delivery in excess of IV dosing for approximately 48 h after intervention. Exponential decay demonstrates rapid removal of drug to near undetectable levels in bone, plasma, and local soft tissue thereafter in a rat model. Local delivery may generate concentrations exceeding that achievable by steady state systemic dosing for 48 h.